Social construction of hand hygiene as a simple measure to prevent health care associated infection - Cole, Mark (2014)
The incidence of Heath Care Associated Infection is a major patient safety concern in the United Kingdom and reducing the morbidity and mortality associated with this has become a National Health Service priority. It is generally accepted that this objective will require a multi-factorial approach where infection prevention and control is seen as everybody’s business. However, some strategies receive greater exposure than others and hand hygiene is widely touted as a common sense solution to a complex problem. This discourse based study combined the techniques of Corpus Linguistics with Critical Discourse Analysis to explore the Textual, Discursive and Sociocultural features of hand hygiene discourse. This took place across three language domains, the Academy, the Newspaper Media and Organisational Policy Makers. These three cultural elites take a consistent account of the problem and the solution. Broadly hand hygiene is portrayed as effective, compliance is basic, performance is poor and Health Care Workers should be held to account through zero tolerance policies and if necessary disciplinary action. However, not only does this background the messy, contextual factors of implementing a hand hygiene policy it imposes a one size fits all approach and measurement programme on compliance that hides the true nature of performance and this ultimately impacts on patient care. This study calls for junior clinicians for whom policy has the greatest impact to become more engaged in the policy making process. In a spirit of openness trusts should adopt linguistic devices that recognise the dynamic nature of practice and a more educational, sophisticated approach to audit.